The Studi Literatur: Media Tabel Inventarisasi sebagai Strategi Pembelajaran Menulis Teks Laporan Hasil Pengamatan: Penggunaan Tabel Inventarisasi dalam Menulis Teks Laporan Hasil Pengamatan - Nurwati Fauziah Nurwati; Dian Indihadi (STKIP Subang, 2026)
This study examines the use of an inventory table as a learning medium in improving students’ ability to write observation report texts. Writing observation report texts is one of the important skills in Indonesian language learning; however, many students still experience difficulties in organizing observation data and developing it into a systematic report. Therefore, an appropriate learning strategy is needed to help students structure the information obtained from observations. The purpose of this study is to analyze the potential of the inventory table as a learning strategy in teaching observation report text writing. This research uses a literature review method by analyzing various scientific articles, books, and previous research related to writing skills, learning media, and observation report texts. The data were collected through documentation techniques and analyzed using descriptive qualitative analysis. The results of the study indicate that the use of learning media plays an important role in improving students’ writing skills. Several studies show that visual and structured media can help students organize information more effectively. In this context, the inventory table can facilitate students in recording, grouping, and organizing observation data systematically, which ultimately supports the process of writing observation report texts more clearly and coherently.